pH-Dependant Antifungal Activity of Valproic Acid against the Human Fungal Pathogen Candida albicans - Chaillot, Julien; Tebbji, Faiza; García, Carlos; Wurtele, Hugo; Pelletier, René; Sellam, Adnane (Frontiers in Microbiology, 2017)
Current antifungal drugs suffer from limitations including toxicity, the emergence of resistance and decreased efficacy at low pH that are typical of human vaginal surfaces. Here, we have shown that the antipsychotic drug valproic acid (VPA) exhibited a strong antifungal activity against both sensitive and resistant Candida albicans in pH condition similar to that encountered in vagina. VPA exerted a strong anti-biofilm activity and attenuated damage of vaginal epithelial cells caused by C. albicans. We also showed that VPA synergizes with the allylamine antifungal, Terbinafine. We undertook a chemogenetic screen to delineate biological processes that underlies VPA-sensitivity in C. albicans and found that vacuole-related genes were required to tolerate VPA. Confocal fluorescence live-cell imaging revealed that VPA alters vacuole integrity and support a model where alteration of vacuoles contributes to the antifungal activity. Taken together, this study suggests that VPA could be used as an effective antifungal against vulvovaginal candidiasis.